An Efficient Terahertz Antenna using CPW Interdigital Capacitor - Das S.; Ghosh S.; Samantaray D.; Bhattacharyya S. (My University, 2025)
In this paper, performance of a conductor backed coplanar waveguide (CPW) interdigital capacitor based microstrip patch antenna at the terahertz frequency range has been analysed. The evolution of the proposed design prototype has been discussed with all the necessary steps. The proposed antenna is designed to radiate over the bandwidth of 280 GHz lying between the frequency range between 5.28 THz and 5.56 THz with realized gain close to 10 dB at resonant frequency of 5.41 THz. The ground and radiating element of antenna have been made using gold and silicon dioxide is employed as substrate material. The antenna simulation has been performed by using CST Microwave Studio. The proposed antenna can be used in medical purposes such as detection of tumour and cancerous cells as well as detections of explosives. © 2018 IEEE.